PENGGUNAAN ARBITRAGE PRICING THEORY UNTUK KEPUTUSAN INVESTASI - Zaroni . (Bina Ekonomi, 2010)
Risk and return are two important things in investing. A good understanding of how risk is predicted to achieve the expected level of return will provide the optimal investment portfolio. In each of the expected return of an investment is always risky. Determination of risk and return to a central issue in asset pricing theory. The financial and investment experts have developed a model of asset pricing  theory (APT) to determine  the risk and return  in the balance of investment  portfolio selection. APT has been a focus of interest in financial and investment studies in the last few decades. APT starts by making the assumption that security returns associated with a number of factors. Factor based models of risk  factors that affect expected return securities.  The factors that generate these returns either the number or type unknown.  Usually represents economic indicators and does not specifically reflect the characteristics of the company. APT as a model must be built on the basis of the assumptions that underlie  the workings of the model. A good understanding of the assumptions underlying the Apr model and how the workings of these models will allow us to use these models with good  investment  decisions.Key words: Return, Risk, Factor Model, Asset pricing Theory (APT)